The proportion of deposited urine patch intercepted by a delayed inhibitor application. Issue 24 (28th October 2022) - Giltrap, Donna; Portegys, Nicolaas; Saggar, Surinder; Hanly, James
ABSTRACT: Nitrification inhibitors can reduce nitrous oxide (N2 O) emissions and nitrate leaching losses from agricultural soils. Technologies have been developed to detect and target urine patches for inhibitor application, thereby reducing the total amount of inhibitor used. However, in practice there will be a time delay between the urine deposition and inhibitor application, potentially leading to physical separation of the inhibitor and urine that could reduce the effectiveness of the inhibitor compared to when the inhibitor and urine are well mixed. In this study, 2L of cattle urine was applied on two soil types in New Zealand. Twenty-four hours later the inhibitor dicyandiamide (DCD) was applied. The soil was sampled within 18 h and again after a rainfall event. DCD concentrations were measured in the 0–20 mm, 20–50 mm, and 50–100 mm depth ranges. The movement of the urine in the soil was simulated using the HYDRUS model. Before the rain most of the DCD was within the top 20 mm and intercepted 21–29% of the urine. After the rainfall event the DCD concentration decreased in the 0–20 mm layer and increased in the 20–50 mm layer. 18–55% or 63-79% of the urine was intercepted by DCD at a concentration of >4 ppm using the measured and modelled DCD concentrations, respectively. However, only 0–27% or 0-53% of the urine was intercepted at a DCD concentration >10 ppm. GRAPHICAL ABSTRACT: UF0001